Project-based Learning in science dissemination with university students of plant biotechnology - Poveda Arias, Jorge (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
At present, the European population sees more risks than benefits in the use of transgenic plants in food. Through the development of a learning strategy based on science dissemination projects (articles and talks) by university students, an increase in autonomous knowledge and vocations in science popularisation has been identified. On the other hand, the development of outreach talks for pre-university students has increased the knowledge of outreach and plant biotechnology, promoting the future choice of higher studies in biotechnology.